Philosophical Ideas in Islam: The Attitude of Ibn Khaldun - Abdul Mukti, Mohd. Fakhrudin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Ibn Khaldun (d. 1406) was one of the Muslim prominent scholars who discussed the position of philosophy in Islam especially after the polemics that took place between Ibn Rushd (d. 1198) and al-Ghazali (d. 1111) on the matter. He referred to the history of philosophical sciences that originally covered all branches of knowledge such as physics and mathematics with their divisions. In the context of philosophy in Islam, he questioned the effectiveness of the sciences of logics and metaphysic to achieve the absolute truth. In this case as al-Ghazali, he refused rational application solely on issues related to divinity as does the mutakallimin. Ibn Khaldun also appreciated the contribution of the Greek and Muslim philosophers in fanning sciences and humanities that have contributed to the history of universal civilization. And this surely stands in line with the religion of Islam which is very dynamic, progressive and open to any process of modernization that al-ummah should be committed with consistently.